LIMITATIONS ON THE FREEDOM OF ASSOCIATION, GATHERING, AND EXPRESS OPINION IN INDONESIA’S STATE SYSTEM - Fakhriy Ilmullah; Mohammad Syaiful Aris (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this study is to explain the concept of the right to freedom of association, assembly and expression of human rights as outlined in Perppu No. 2 of 2017 concerning Community Organizations. The method used in this study is normative using the statutory approach, concept approach, and case approach. The results of the study revealed that the concept of human rights contained non -ograble rights and derogable rights, the government through the House of Representatives (DPR) ratified the Civil Society Organization Regulation into Law No. 16 of 2017 restricts the right to freedom of association, association, and issuing opinions based on certain conditions previously stated. This study will benefit restrictions on freedom of association, assembly, and issuing opinions in the constitutional system in Indonesia are regulated in government regulations in lieu of law (PERPPU) Number 2 of 2017 concerning social organizations. In Perppu No. 2 of 2017 Concerning CSOs, there are several provisions that limit the freedom of Indonesian citizens to exercise their rights, namely the right to associate, gather, and express opinions. The right to freedom of association, gathering, and issuing opinions is regulated in the Perppu on Civil Society Organizations, Law No. 16 of 2017 concerning the enactment of Civil Society Organization Regulation.